Proximal Tibia and Fibula Fragility Fracture Complicated by Anticoagulation and Demand-Mediated Myocardial Infarction - Mendelson, Daniel (SAGE Publications, 2011)
We present for discussion a case of a right displaced proximal metaphyseal tibial fracture with intraarticular extension and a same-level proximal fibula fracture with severe degenerative arthritis in a medically complex 89 year old community dwelling woman with a history of paroxysmal atrial fibrillation, right lower extremity deep venous thrombosis 1 month prior to this admission on warfarin, obesity, peripheral vascular disease, and previous stroke. Her course is complicated by demand-mediated myocardial infarction. This case demonstrates that comanagement can lead to minimal delays and a satisfactory outcome in a complex, high-risk patient.